Efficiency of 7-dehydrocholesterol vitamin-D3 complex cream for xerosis and pruritus in elderly women - Yahya, Yulia Farida; Rahmadini, Meirina; Jatmiko, Pandu Haryo; Emirzon, M. Afif Baskara; Nabila, Dewa Ayu Bulan; Kurniawati, Yuli; Toruan, Theresia Lumban; Riviati, Nur (Journal of General - Procedural Dermatology and Venereology Indonesia, 2024)
Background: Xerosis and pruritus (XP) are the most common skin conditions in the elderly, manifesting clinically as roughness, scales, fissures, and mild-to-severe itching. Vitamin D improves skin hydration, transepidermal water loss (TEWL), and regulates the immune system. We aimed to determine the efficiency of topical 7-dehydrocholesterol (DHC)-vitamin D3 complex cream in elderly patients with XP. Methods: An experimental phase III study was performed on elderly women with XP from December 2021 to March 2022 at the Geriatric Dermatology Clinic of Dr. Mohammad Hoesin General Hospital, Palembang. Inclusion criteria were age older than 55 years, healthy or with comorbidity. The exclusion criteria include the use of moisturizer within two weeks before the study. DHC-vitamin D3 cream was applied on subject’s volar arms once a day. Overall dry skin score (ODSS), visual analog scale (VAS) for pruritus and adverse effects, skin hydration, TEWL, sebum level, serum vitamin D level, and dermatology life quality index (DLQI) were assessed at baseline and after 4 weeks. Statistical analysis was done with Wilcoxon and paired T-test. Results:Eighteen elderly women were included. Most subjects were 60 to 74 years old (83,3%). Half the subjects (50%) had comorbidity. There was a significant difference in skin hydration (p Conclusion: Topical 7-DHC vitamin D3 complex cream is proven to improve skin barriers, increase serum vitamin D levels, well-tolerated, and provided satisfaction and comfort in elderly women with XP.